Faktor-faktor Penentu Perilaku Investor dalam Transaksi Saham di Surabaya - Iramani, Rr.; Bagus, Dhyka (Jurnal Aplikasi Manajemen, 2008)
This aim study to explore factors determinant investors behavior in stock exchange transaction in Surabaya. Furthermore, this study test psychological difference between male and female investor. To test hypotheses, this study employs factor analysis and independent sample t-test. By performing Factor Analysis, this study reveals six factors determine investor behavior named: security and pleasure factor, bias thinking factor, bravery factor, social and emotional interactionfactor and judgement bias factor. More over, by performing independent sample t-test, this study found that there is not psychological difference between male and female investor.